2018
DOI: 10.1590/1808-1657001022017
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Tween 80 on laccase production by Pleurotus sajor-caju and the efficiency of crude enzyme broth in the removal of bisphenol-A

Abstract: Bisphenol-A is currently considered an environmental pollutant, capable of interfering in the endocrine system of organisms and causing alterations in its development and reproductive system. An alternative method to the chemical treatment of this pollutant has been the use of oxidative enzymes, especially laccases produced by fungi. In order to reduce production costs, agro-industrial waste can be used in the culture medium composition. Nonionic surfactants, which are only slightly toxic to biological membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…In addition, it was also found that Tween 80 was degraded by L. theobromae (Cao et al, 2020). Teodoro et al (2018) reported that the addition of Tween 80 to the culture medium enhanced laccase activity during the degradation of bisphenol A by Pleurotus sajor-caju. Nielsen et al (2016) found that the addition of Tween 80 (0.1%) to growth media increased the growth rate of Staphylococcus aureus batch cultures, and it also increased the total biomass when S. aureus was grown as biofilms.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, it was also found that Tween 80 was degraded by L. theobromae (Cao et al, 2020). Teodoro et al (2018) reported that the addition of Tween 80 to the culture medium enhanced laccase activity during the degradation of bisphenol A by Pleurotus sajor-caju. Nielsen et al (2016) found that the addition of Tween 80 (0.1%) to growth media increased the growth rate of Staphylococcus aureus batch cultures, and it also increased the total biomass when S. aureus was grown as biofilms.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, It has been reported that laccase showed its maximum value at a Tween 80 concentration of 0.1% (Elsayed et al, 2012). Similarly, the addition of Tween 80 to the culture medium enhanced laccase activity during the degradation of bisphenol A by Pleurotus sajor-caju (Teodoro et al, 2018). In particular, Tween 80 has been shown to be a laccase inducer in Pleurotus eryngii grown in solid state fermentation (Akpinar & Ozturk, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, similar enhancements can also occur in the oxidation of other large molecular substrates, such as biodegradation of lignin by linoleic acid, arachidonic acid, and Tween 80 or Tween 20 36 – 39 , cellulose digestibility 40 , 41 and biobleaching hardwood kraft pulp 42 . Additionally, degradation of other organic pollutants can also be enhanced by Triton X-100, including indole 43 , bisphenol A 44 , 45 , phenol 46 48 , fungicide miconazole and antidepressant 49 , and asphalt 50 . As a result of lipid peroxidation reactions, the unstable α -position of ether oxygen bond (–C–O–C–) in Tween 20, carbon–carbon double bond (C=C) and that in Tween 80 should be also considered.…”
Section: Resultsmentioning
confidence: 99%